Amazing optical illusions : over 250 illustrations - Sarcone, Gianni A.; Waeber, Marie J. (London : Carlton; Sevenoaks, 2005)
Are your eyes and brain ready for a challenge? Then hold on tight because these picture puzzles will blow your mind! Through a clever use of color, angles, and ambiguity, they trick your perception and confound your sense of reality. Watch as ladybugs seem to walk in circles on the page and a nest of vipers uncoils. Look out a window and gaze at the view$1 (Bor is that a painting of a view from a window? How is it possible? Detailed explanations reveal the science behind the visual effects, letting you know what you$1 (Bre seeing and why you see it that way. Amazing Optical Illusions presents a range of deceptive images, impossible objects, and incredible worlds, all in a cutting-edge style that is instantly engaging.s
"Over 150 illustrations"
Keywords: Optical illusions